2021
DOI: 10.3233/jad-210617
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Evaluation Informs Understanding of Motor Cognition and Therapies in Older Adults with Mild Cognitive Impairment

Abstract: Background: 10%to 20%of Americans aged 65 and older have mild cognitive impairment (MCI) with 10%progressing to Alzheimer’s disease (AD) each year. Underserved groups, including African Americans (AAs), are among the most vulnerable to MCI and AD. Although evidence continues to amass, the benefits of exercise and movement for AD is still understudied in AD. Objective: Understanding the attitudes, perceptions, and beliefs about motor-cognitive integration and examining the physical activity of a sample of predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The association of Black/African American race with moderate or severe cognitive dysfunction coincides with previous reports indicating that older Blacks/African Americans may be more vulnerable to mild cognitive impairment. [27] The association of Black/African American race with cognitive impairment may be due to underlying more severe AD. Indeed, previous studies found more persistent and severe AD in Black/African American children.…”
Section: Discussionmentioning
confidence: 99%
“…The association of Black/African American race with moderate or severe cognitive dysfunction coincides with previous reports indicating that older Blacks/African Americans may be more vulnerable to mild cognitive impairment. [27] The association of Black/African American race with cognitive impairment may be due to underlying more severe AD. Indeed, previous studies found more persistent and severe AD in Black/African American children.…”
Section: Discussionmentioning
confidence: 99%
“…Transcripts were analyzed in NVivo 12 software (Lumivero; Denver, CO). As in Lazris et al, [10], we applied a combined deductive and inductive analysis approach to extract themes and sub-themes from both focus group transcripts. We first organized the major topics pre-defined by the focus group guide (Table 4) into a deductive codebook.…”
Section: Methodsmentioning
confidence: 99%
“…While no effective therapies currently exist to prevent MCI from progressing to Alzheimer's Disease (AD) [3], movement therapies integrating music and dance offer an effective, non-pharmacological option to offset cognitive decline [4,5]. Such therapies are especially promising, as they couple physical activity with high cognitive engagement to mitigate the declines in motor-cognitive integration that manifest as impaired daily functioning [6][7][8][9][10]. However, stronger methodological rigor is needed to effectively implement these therapies for every individual, thus likely requires additional therapeutic parameters [11].…”
Section: Individuals With Mild Cognitive Impairment (Mci) Present Mea...mentioning
confidence: 99%